Prediction of resident performance ratings and board examination scores from medical school grade point average and interview scores during resident selection - N. Chierakul (2020)
© 2019, Medical Association of Thailand. All rights reserved. Objective: To evaluate the association between performance before entering the program and the outcomes of post-graduate medical residency training. Materials and Methods: The selection process scores of 42 applicants for the internal medicine residency program at Siriraj Hospital in academic year 2011 were extracted. The scores consisted of undergraduate grade point average (GPA) during the clinical training years and interview performance during the application process. Association between scores from the selection process and scores from both multisource feedback during training and board certification examinations were then examined. Multiple regression analysis was performed to identify factors associated with training outcomes. Results: The mean ± standard deviation (SD) undergraduate GPA during the clinical training years was 85.5±6.8, and mean interview performance score was 88.6±4.1. Undergraduate GPA scores during the clinical years had modest correlation with faculty rating scores (r=0.449, p=0.003), and good correlation with written examination scores (r=0.693, p<0.001). Interview performance scores had modest correlation with faculty rating scores (r=0.515, p<0.001), nurse rating scores (r=0.432, p=0.004), and written examination scores (r=0.468, p=0.002). In multivariate analysis, undergraduate GPA scores and interview performance scores were independently associated with training outcomes. Conclusion: Interview performance as part of a resident selection process has additive effect to previous academic background for predicting future success in residency training.